A.S.P.E.N. Clinical Guidelines: Nutrition Support of Adult Patients With Hyperglycemia. Issue 1 (29th June 2012) - McMahon, M. Molly; Nystrom, Erin; Braunschweig, Carol; Miles, John; Compher, Charlene; ,
Abstract : Background : Hyperglycemia is a frequent occurrence in adult hospitalized patients who receive nutrition support. Both hyperglycemia and hypoglycemia (resulting from attempts to correct hyperglycemia) are associated with adverse outcomes in diabetic as well as nondiabetic patients. This American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) Clinical Guideline summarizes the most current evidence and provides guidelines for the desired blood glucose goal range in hospitalized patients receiving nutrition support, the definition of hypoglycemia, and the rationale for use of diabetes‐specific enteral formulas in hospitalized patients. Method : A systematic review of the best available evidence to answer a series of questions regarding glucose control in adults receiving parenteral or enteral nutrition was undertaken and evaluated using concepts adopted from the Grading of Recommendations, Assessment, Development and Evaluation working group. A consensus process was used to develop the clinical guideline recommendations prior to external and internal review and approval by the A.S.P.E.N. Board of Directors. Results/Conclusions : 1. What is the desired blood glucose goal range in adult hospitalized patients receiving nutrition support? We recommend a target blood glucose goal range of 140–180 mg/dL (7.8–10 mmol/L). (Strong) 2. How is hypoglycemia defined in adult hospitalized patients receiving nutrition support? We recommend that hypoglycemia be defined as a blood glucose concentration of <70 mg/dL (<3.9 mmol/L). (Strong) 3. Should diabetes‐specific enteral formulas be used for adult hospitalized patients with hyperglycemia? We cannot make a recommendation at this time.